HYDROGEOPHYSICS TECHNIQUES TO AQUIFER LOCATING AND MONITORING FOR INDUSTRIAL ZONE NORTH THANGLONG AND QUANGMINH, HANOI - Giang, Nguyen Van; Duan, Nguyen Ba; Thanh, Le Ngoc; Hida, Noboru (Vietnam Journal of Earth Sciences, 2014)
Geophysical methods were applied for hydrogeological targets in many countries including Vietnam. This paper resents results of using complex geophysical techniques as well as 2D electrical resistivity imaging (ERI), vertical electrical sounding (VES), very low frequency (VLF) and seismic refraction for geological structure investigation to aquifers locate and to assess of hydrogeological condition for groundwater potential in North Thanglong and Quangminh industrial zones, Hanoi, Vietnam. The locations of two aquifers are determined by their depth and thickness on the basis of resistivity and seismic velocity values which were proved by stratifications of three boreholes to 40-60m of depth on study area. There are connecting from surface water to shallow aquifer by hydraulic windows from VLF data. The deeper aquifer can be considered as potential groundwater for supplying in the area. Groundwater level, electrical conductivity and water temperature were measured in six monitoring wells, complemented by anion, cation and stable isotope analyses of ground and surface water. This study also reviews, compiles and comprehensively analyzes spatiotemporal variations of hydrological and hydrogeological characteristics of shallow and deep groundwater aquifers in area and in nearby Red River water. The results show that groundwater in both shallow and deep aquifers was fresh, but mainly calcium-bicarbonate type. With the goal of devising sustainable water use regulations, more research must be directed toward long-term monitoring of groundwater and surface water quality, as well as toward detailed investigation of the hydraulic characteristics of local aquifers in the study area. References AGI, 2003. The SuperSting with Swift automatic resistivity and IP system instruction manual, Advanced Geosciences, Inc., Austin, Texas, U.S.A. Lê Đức An, 1996. Sự dao động của mực nước biển vùng thềm lục địa Việt Nam. Tc. Các KH về TĐ, T.18, (4), 365-367. J. Asfahani and B. A. Zakhem, 2013. Geoelectrical and Hydrochemical Investigations for Characterizing the Salt Water Intrusion in the Khanasser Valley, Northern Syria, Acta Geophysica vol. 61, no. 2, Apr. 2013, 422-444 DOI: 10.2478/s11600-012-0071-3. G. Beziuk, 2012. Near Surface Geophysical Surveys with a High Frequency Mutual Impedance Measuring System, Acta Geophysica vol. 60, no. 1, Feb. 2012, 140-156 DOI: 10.2478/s11600-011-0064-7. Bui D D, Kawamura A, Tong T N, Amaguchi H, Nakagawa N, 2012. Spatio-temporal analysis of recent groundwater-level trends in the Red River Delta, Vietnam. Hydrogeology Journal 20: 1635-1650 DOI 10.1007/s 10040-012-0889-4. Dan N V, Dzung N T, 2002. Current status of groundwater pollution in Hanoi area. Proceedings of the International Symposium on Environment and Injure for Community Health Caused by Pollution during the Urbanization and Industrialization. Hanoi Dec. 28-29, 2002. VNU Hanoi, p.55-69. P. Derecke, 1980. The generalized reciprocal method of seismic refraction interpretation, Society of Exploration Geophysicists, 104. Nguyễn Địch Dỹ, 1998. Nghiên cứu quy luật địa tầng Đệ Tứ ở Việt Nam và một số đề xuất. TC. Các KH về TĐ, T.20, (4), 258-265. Fagin S.W., 1991. Seismic modelling of geologic structures: Applications to Exploration problems. Geophysical Development, V. 2, SEG, 3-92. N.V. Giang, T.D. Nam, M. Bano, 2012. Groundwater investigation on sand dunes area in southern part of Vietnam by Magnetic Resonance Sounding, Acta Geophysica vol. 60, no. 1, 157-172 DOI: 10.2478/s11600-011-0064-7. N. V. Giang, 2005. Application of Geophysical Methods for Engineering Geology in Vietnam. Advances in Natural Sciences, vol. 5, no. 3, 325-332. Nguyễn Văn Giảng, 1998. Kết quả bước đầu quan sát ô nhiễm môi trường nước dưới đất ở Hà Nội bằng số liệu địa điện. TC Các KH về TĐ, 20(1), 21-26. Golonka J, Krobicki M, Pajak J, Giang NV, Zuchiewicz W, 2006. Global plate tectonics and paleogeography of southeast Asia. AGH University of Science and Technology, Arkadia, Krakow, Poland pp. 1-128, ISBN 83-88927-10-8. Griffiths D.H. and King R.F., 1986. Applied geophysics for geologists & engineers. Pergamon Press, Inc., 240. Guerin R., 2005. Borehole and surface-based hydrogeophysics. Hydrogeology J., 13(1), 251-254. H. Haynes, A.M. Ockelford, E. Vignaga and W.M. Holmes, 2012. A New Approach to Define Surface/Sub-Surface Transition in Gravel Beds, Acta Geophysica vol. 60, no. 6, Dec. 2012, 1589-1606 DOI: 10.2478/s11600-012-0067-z. V. H. Hiếu, L.T.P.Quỳnh, Josette G, Etcheber H, D.T. Thúy, H.T. Cường, 2012. Bước đầu khảo sát hàm lượng carbon hữu cơ không tan (POC) trong môi trường nước vùng hạ lưu hệ thống Sông Hồng. TC. Các KH về TĐ, T. 34, (1); 65-69. Hori K., Tanabe S., Saito Y., Haruyama S., Viet N., Kitamura A., 2004. Delta initiation and Holocene sea-level change: Example from the Red river delta, Vietnam. Sed. Geol., 164, 237-249. Hubbard S.S., Rubin Y., 2000. Hydrogeological parameter estimation using geophysical data: a review of selected techniques. J. of Contaminant Hydrology 45, 3-34. Hubbard S.S., Rubin Y.,Majer E., 1999. Spatial Correlation Structure Estimation Using Geophysical and Hydrogeological Data. Water Resources Research, 35, 1809-1825. Karous M., Hjelt S.E., 1983. Linear filtering of VLF dip-angle measurements. Geophysical Prospecting, 31, 782-894. Keller G.V. and Frischknecht F.C., 1966. Electrical methods in geoelectric prospecting, Pergamon Press, Inc., 517. Loke. M. H., 2004. Tutoral: 2-D and 3-D electrical imaging survey. Trần Nghi, Ngô Quang Toàn, 1991. Đặc điểm chu kỳ trầm tích và lịch sử tiến hóa địa chất Đệ Tứ của châu thổ Sông Hồng, Tạp chí Địa chất số 206-207, tr. 65-77. Ogilvy, R.D. and Lee, A.C., 1991. Interpretation of VLF-EM in-phase data using current density pseudo-sections. Geophysical Prospecting, 39, 567-580. Owen, S.J.; Jones, N.L., and Holland, J.P., 1996. A comprehensive modeling environment for the simulation of groundwater flow and transport. Engineering with Computers 12 (3-4), 235-242. doi:10.1007/BF01198737. F. F. Pedersen, N.V. Giang, 2002. Saltwater Intrusion in Aquifer-TEM Mapping around Gialoc-Haiduong, Vietnam. Advances in Natural Sciences, Vol.3, No.3, 289-295. Pham V. N., D. Boyer, N. T. K. Thoa, N.V.Giang, 1994. Deep Ground water Investigation in South Vietnam by Combined VES/MTS Methods, Ground Water, vol.32, N.4, July-August, 675-683. Rangin C, Klein M, Roques D, Le Pichon X and Trang L V, 1995. The Red river fault system in the Tonkin Gulf, Vietnam. Tectonophysics, 243; 209-222. Rubin Y. and Hubbard S.S, 2005. Hydrogeophysics, Series: Water Science and Technology Library, Springer, Vol. 50, 523. Sandberg S.K., Slater L.D., Versteeg R., 2002. An integrated geophysical investigation of the hydrogeology of an anisotropic unconfined aquifer. J. of Hydrology. 267, 227-243. Telford, W.M.; L.P. Geldart, R.E. Sheriff, 1990. Applied Geophysics (2nd ed.), 480. Vickery A., Hobbs B.A., 2003. Resistivity imaging to determine clay cover and permeable units at an ex-industrial site. Near Surface Geophys., 1, 21-30. WTO, 2004. Guidelines for drinking water quality; Training Pack, WTO, Geneva, Switzerland.